1989
DOI: 10.1159/000234758
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interleukin 4 and Gamma Interferon in the Regulation of Human IgE Synthesis: Possible Alterations in Atopic Patients

Abstract: The IgE helper function of human T cell clones or their phytohemagglutinin-induced supernatants was positively correlated with their ability to produce or their content in interleukin 4 (IL-4), whereas it was inversely correlated with production of or content in gamma interferon. The addition to B cell cultures of anti-IL-4 antibody abolished not only the IgE synthesis induced by recombinant human IL-4, but also that induced by IL-4-producing T cell clones or their phytohemagglutinin-induced supernatants. A cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…In the murine system, IgE synthesis is controlled by two T helper cell subsets, Thl and Th2, which exhibit different cytokine production profiles [2], Similar observations have been established in humans [3][4][5], Interleukin (lL)-4 derived from the Th2 subset in duces class switching to IgE production in B lymphocytes [5,6], while interferon (IFN)-y derived from e.g. Thl cells inhibit it [7], Flolt et al [8] have demonstrated that the IFN-y-producing capacity of CD4+ T cell clones from young children is reduced relative to adults.…”
Section: Introductionsupporting
confidence: 54%
“…In the murine system, IgE synthesis is controlled by two T helper cell subsets, Thl and Th2, which exhibit different cytokine production profiles [2], Similar observations have been established in humans [3][4][5], Interleukin (lL)-4 derived from the Th2 subset in duces class switching to IgE production in B lymphocytes [5,6], while interferon (IFN)-y derived from e.g. Thl cells inhibit it [7], Flolt et al [8] have demonstrated that the IFN-y-producing capacity of CD4+ T cell clones from young children is reduced relative to adults.…”
Section: Introductionsupporting
confidence: 54%
“…It bas been proposed tbat there is a genetically determined defect in T lymphocytes of allergic subjects which leads to an upset in the control of IgE antibody production [8]. Animal, and now human studies, bave shown that there are differences in T-cell generation of the peptide regulators interleukins 4 and 5 between allergic and nonallergic individuls [9,10]. As interleukin 4 is an essential factor for the induction of IgE synthesis and interleukin 5 stimulates eosinophil proliferation and activation, these may be looked upon as pivotal in the generation of allergy and asthma.…”
Section: Host Defectsmentioning
confidence: 99%
“…However, contrary to the optimal IL-4 concentrations used in vitro, less IL-4 may be available in normal individuals in vivo. On the other hand, the atopic status is likely to be associated with a high endogenous IL-4 secre tion because of an increased frequency of IL-4-producing T helper cells in atopies [13]. To our knowl edge, no data have so far been available on IL-4 and IFN-y serum concentrations in atopic versus normal persons.…”
mentioning
confidence: 99%